2016
DOI: 10.1088/0957-4484/27/44/445702
|View full text |Cite
|
Sign up to set email alerts
|

Development of a novelin silicomodel of zeta potential for metal oxide nanoparticles: a nano-QSPR approach

Abstract: Once released into the aquatic environment, nanoparticles (NPs) are expected to interact (e.g. dissolve, agglomerate/aggregate, settle), with important consequences for NP fate and toxicity. A clear understanding of how internal and environmental factors influence the NP toxicity and fate in the environment is still in its infancy. In this study, a quantitative structure-property relationship (QSPR) approach was employed to systematically explore factors that affect surface charge (zeta potential) under enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…Hence, the 7‐variable model was selected as the most accurate for the entire set. Its ratio of the number compounds and variables in the model ensured the avoidance of overfitting, which is still within the 5:1 rule …”
Section: Resultsmentioning
confidence: 97%
“…Hence, the 7‐variable model was selected as the most accurate for the entire set. Its ratio of the number compounds and variables in the model ensured the avoidance of overfitting, which is still within the 5:1 rule …”
Section: Resultsmentioning
confidence: 97%
“…We initially extracted more than 150 data points; however, after data curation (as is described in Materials and Methods section), we included in the reliable dataset 87 zeta potential measurements from 12 literature sources ( Table 1 ) [ 1 , 12 , 18 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…The QSPR has been widely applied over the last decade to predict nanoparticle properties [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. To date, only three research articles have reported QSPR modeling of zeta potentials [ 17 , 18 , 19 ]. These nano-QSPR models focused only on chemical composition-dependent descriptors [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16][17] Wyrzykowska et al developed a nano-QSPR model to predict the zeta potential of MONs in KCl aqueous solution of MONs. 18 In this study, we developed a nano-QSPR model, considering different crystalline types and sizes, to predict band gaps of MONs. Besides, band gaps were also calculated by two other estimation methods to compare the predictive ability of different methods.…”
Section: Introductionmentioning
confidence: 99%